(untitled) (Italian Journal of Public Health, 2010)
Background: The relationship between suicide and alcohol consumption is well established at the individual level. In this article we examine this relationship at a national level across 98 different countries. Methods: The suicide and alcohol consumption rates considered were those calculated by the WHO (2008 and 2004 database respectively). A simple correlation analysis was conducted and cross-national variations were shown in cartograms with the values of the standard deviation as class breaks. Results: A significant positive association (r = 0.42 in the case of men, r = 0.34 in the case of women) emerged between per capita alcohol consumption and gender-specific suicide rates when we considered all the 98 countries around the world for which data were available. When considering the group of ex-communist countries alone, the correlation coefficient between alcohol consumption and suicide rates was higher and statistically significant for both men (0.51) and women (0.47). Conclusions: Bivariate analysis at the country level delineates a worldwide association between suicide rates and alcohol consumption. There were no countries where a high or moderate-high alcohol consumption rate coincided with a low or medium-low suicide rate. Where alcohol consumption is high, there is an impact on suicide rates. Where it is low, this seems to have a protective effect, unless other suicide determinants acquire a major role. Suicide is multi-factorial and the determinants may be different in any given country, multivariate analysis and local studies are therefore required.